SC59 Critical of care: is the intensive care unit appropriate for in-situ simulation?. (3rd November 2019) - Glaze, Steffan; Edwards, Alexandra; Navaneetham, Krishna; Whitehead, Andrew; Jacques, Andrew
Abstract : Background: The Intensive Care Unit of the Royal Berkshire Hospital, Reading, is a 17-bedded general critical care unit with over 1000 admissions per year. Since 2015, multidisciplinary in-situ simulation has been delivered approximately twice per month and is now a well-established part of the unit's education programme. In-situ simulation continues to develop as an educational tool (Rosen et al, 2012), and has been shown to be effective in the critical care setting (Theilen et al 2017). Summary of work: In-situ simulation forms part of a weekly teaching programme on the Intensive Care Unit. Scenarios are led by a consultant intensive care physician with experience in delivering simulation education. They are supported by a member of junior medical staff working in a clinical fellow post with an emphasis on simulation and education. Doctors and nurses participate in each session, occasionally with allied health professionals. Simulation is delivered using a mannequin with monitoring in an empty clinical bed space. Participants use actual equipment and medications (with the exception of controlled drugs). Scenarios cover a broad range of topics, from high frequency events to infrequent medical emergencies (e.g. intubation of a septic patient with pneumonia, obstructed and/or displaced tracheostomy). The debrief covers the clinical aspects with a strong focus on the human factors, team working and practical issues. Participants and observers are invited to provide feedback following the sessions. Summary of results: Over 70 feedback responses have been collected over the course of the programme to date. Respondents are consistently positive, agreeing that the scenarios are relevant, useful for learning and improve confidence. Free-text responses frequently referred to realism, learning about team work and the benefit of practicing infrequent emergencies. Improvements suggested included removing observers from the bed space to avoid confusion, clarity of what equipment can be used and the opportunity to improve fidelity with mock patients on the electronic patient record. Discussion, conclusions and recommendations: In-situ simulation is an acceptable and useful format for teaching in the intensive care unit. Learning for staff covers both the clinical topic of the emergencies, as well as human factors. Future initiatives will aim to improve patient safety further by acting on latent threats identified during simulations, developing scenarios in response to safety incidents reported locally and nationally, and identifying risks associated with the physical structure of the area. References: Rosen, M. A., Hunt, E. A., Federowicz, M. A. & Weaver, S. J., . In situ simulation in Continuing Education for the Health Care Professions: A Systematic Review. Journal of Continuing Education in the Health Professions 2012, 32(4), pp. 243–254. Theilen, U., Fraser, L., Jones, P., Leonard, P. & Simpson, D., 2 017. Regular in-situ simulation training of paediatric Medical Emergency Team leads to sustained improvements in hospital response to deteriorating patients, improved outcomes in intensive care and financial savings. Resuscitation, 115, pp. 61–67.